Birth Chairs, Midwives, and Medicine. - Banks, Amanda Carson (University Press of Mississippi, 1999)
There was a time when birth was treated as a natural process rather than a medical condition. Before 1800, women gave birth seated in birth chairs or on stools and were helped along by midwives. Then societal changes in attitudes toward women and the practice of medicine made birthing a province of the male-dominated medical profession. In Birth Chairs, Midwives, and Medicine, Amanda Carson Banks examines the history of the birth chair and tells how this birthing device changed over time. Through photographs, artists' renditions of births, interviews, and texts from midwives and early obstet.